Pengembangan Lembar Kerja Peserta Didik Berbasis Hots Pada Pembelajaran Pendidikan Agama Islam Dan Budi Pekerti - Nursita; Tungga', Ummul Budiwati; Muhammad Ikhsan (South Sulawesi Education Development, 2025)
This study aims to develop Student Worksheets (LKPD) based on higher-order thinking Skills (HOTS) in Islamic Religious Education and Character Education learning for grade VIII students at SMPN 3 Palopo. This LKPD was developed to improve students' critical, analytical, and creative thinking skills in understanding learning materials. This study uses the Research and Development (R&D) method with the ADDIE development model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques in this study include observation, interviews, and questionnaires. Data analysis was carried out descriptively, qualitatively, and quantitatively to determine the level of validity, practicality, and effectiveness of the LKPD developed. The results of the study showed that (1) the development of HOTS-based LKPD in Islamic Religious Education and Character Education learning was carried out using the ADDIE model systematically and gradually; (2) the results of the validity test showed that the LKPD developed obtained a validation score of 96% from media experts, 87% from material experts, and 78% from language experts, so it was declared very valid for use; (3) the results of the practicality test show that this LKPD gets a percentage of 88% from teachers, which shows that this LKPD is easy to use and supports interactive and innovative learning processes. In addition, implementing HOTS-based LKPD in Islamic Religious Education and Character Education learning positively impacts student motivation and understanding. Students show increased critical thinking and problem-solving and are more active in learning. Based on these results, it is concluded that the HOTS-based LKPD developed is very valid, practical, and effective for use in Islamic Religious Education and Character Education learning in class VIII of SMPN 3 Palopo.